Inhibition of Kupffer Cell Activity Improves Transplantation of Human Adipose-Derived Stem Cells and Liver Functions. Issue 3 (March 2013) - Hong, Il-Hwa; Han, Seon-Young; Ki, Mi-Ran; Moon, Young-Mi; Park, Jin-Kyu; You, Sang-Young; Lee, Eun-Mi; Kim, Ah-Young; Lee, Eun-Joo; Jeong, Jae-Ho; Kang, Kyung-Sun; Jeong, Kyu-Shik
Numerous approaches to cell transplantation of the hepatic or the extrahepatic origin into liver tissue have been developed; however, the efficiency of cell transplantation remains low and liver functions are not well corrected. The liver is a highly immunoreactive organ that contains many resident macrophages known as Kupffer cells. Here, we show that the inhibition of Kupffer cell activity improves stem cell transplantation into liver tissue and corrects some of the liver functions under conditions of liver injury. We found that, when Kupffer cells were inhibited by glycine, numerous adipose-derived stem cells (ASCs) were successfully transplanted into livers, and these transplanted cells showed hepatoprotective effects, including decrease of liver injury factors, increase of liver regeneration, and albumin production. On the contrary, injected ASCs without glycine recruited numerous Kupffer cells, not lymphocytes, and showed low transplantation efficiency. Intriguingly, successfully transplanted ASCs in liver tissue modulated Kupffer cell activity to inhibit tumor necrosis factor-α secretion. Thus, our data show that Kupffer cell inactivation is an important step in order to improve ASC transplantation efficiency and therapeutic potential in liver injuries. In addition, the hepatoprotective function of glycine has synergic effects on liver protection and the engraftment of ASCs.